2017
DOI: 10.1590/1678-7757-2016-0252
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1% sodium alendronate in the non-surgical treatment of periodontal intraosseous defects: a 6-month clinical trial

Abstract: Background and objectives Few studies have evaluated the effect of the topical application of sodium alendronate (ALN) on the treatment of intrabuccal bone defects, especially those caused by periodontitis. This 6-month randomized placebo controlled clinical trial aimed at evaluating the effect of non-surgical periodontal treatment associated with the use of 1% ALN, through clinical evaluations and cone-beam computed tomography (CBCT).Material and Methods Twenty individuals with chronic periodontitis underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 34 publications
6
26
0
4
Order By: Relevance
“…It is important to reinforce that osteonecrosis of the jaw has been reported as an adverse event associated with the long‐term or systemic use of bisphosphonates . Corroborating our results, studies using low dose topical ALN administration did not present adverse effects . However, future studies should be conducted to assess the potential cumulative effects of topical ALN administration.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It is important to reinforce that osteonecrosis of the jaw has been reported as an adverse event associated with the long‐term or systemic use of bisphosphonates . Corroborating our results, studies using low dose topical ALN administration did not present adverse effects . However, future studies should be conducted to assess the potential cumulative effects of topical ALN administration.…”
Section: Discussionsupporting
confidence: 76%
“…The effectiveness of the topical application of 1% ALN in surgical and non‐surgical periodontal procedures was also investigated in humans. Overall, authors reported additional benefits in PD and CAL improvements with the adjunctive topical use of ALN in comparison with scaling and root planing alone .…”
Section: Introductionmentioning
confidence: 99%
“…Search Results. After selection according to our preestablished protocol, 14 RCTs were included for quantitative meta-analysis [10][11][12][23][24][25][26][27][28][29][30][31][32][33]. The details of search procedure were presented in study flowchart ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Our research resulted in eight studies in which CBCT was used to address the patients' outcomes in relation to periodontal disease. All of the studies are randomized clinical trials [88][89][90][91][92][93][94][95]. Table 4, the CASP (critical appraisal skills program) checklist, was used to assess outcomes.…”
Section: Patient Outcome Efficacymentioning
confidence: 99%
“…Author's contribution: Both authors contributed to the search strategy, studies allocations, and quality assessments of the included studies. Gupta SJ et al 2014 [90] Fiejo et al 2012 [72] Khosropana et al2015 [91] Walter et al 2012 [82] Bhavsar et al 2016 [93] Raichur et al 2012 [84] Pajnigara et al 2017 [94] Marinescu et al 2013 [79] Dutra et al 2017 [89] Qiao et al 2013 [75] Nemoto et al 2018 [95] Haghgoo et al2014 [83] Banodkar et al 2015 [68] Cimbaljevic et al 2015 [69] Darby et al 2015 [70] Li F et al 2015 [74] Guo et al 2016 [73] The results for systematic reviews according to the PRISMA flow chart…”
Section: Consent To Publish: Not Applicablementioning
confidence: 99%